1997
DOI: 10.1046/j.1365-263x.1997.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesiodentes in twins: a case report and a review of the literature

Abstract: This report describes 7-year-old Afro-Caribbean monozygotic twin boys who both presented with bilateral unerupted mesiodentes palatal to the central incisors. There have been two previous similar reports. From this case and previous reports it was concluded that mesiodentes in monozygotic twins are likely to be concordant with respect to the number of supernumerary teeth. Unilateral mesiodens usually have been mirror imaged in each twin. Minor discordance between monozygotic twins is common with respect to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 5 publications
6
40
2
3
Order By: Relevance
“…Conical mesiodens is more common, and is more likely to erupt between the central incisors as a diminutive but fully developed tooth (3-7). In contrast, tuberculate mesiodens tends to develop later and shows incompletely developed roots (2). In the present study, the shape observed was mainly conical (72.9%), which corresponds well with the literature (3)(4)(5)(6)15,17,18).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Conical mesiodens is more common, and is more likely to erupt between the central incisors as a diminutive but fully developed tooth (3-7). In contrast, tuberculate mesiodens tends to develop later and shows incompletely developed roots (2). In the present study, the shape observed was mainly conical (72.9%), which corresponds well with the literature (3)(4)(5)(6)15,17,18).…”
Section: Discussionsupporting
confidence: 92%
“…In this series, 21.1% of the mesiodentes were partially or fully erupted, which is within range of percentages reported earlier (2,7,9).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“….) ont donné lieu à des rapports de cas chez des jumeaux MZ, ce qui renforce l'idée d'une transmission géné-tique [26,44,55,58,59]. …”
Section: Anomalies De Morphologieunclassified